2017
DOI: 10.1002/adma.201606061
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Biofabrication Strategies for Engineering Complex Tissue Constructs

Abstract: The demand for organ transplantation and repair, coupled with a shortage of available donors, poses an urgent clinical need for the development of innovative treatment strategies for long-term repair and regeneration of injured or diseased tissues and organs. Bioengineering organs, by growing patient-derived cells in biomaterial scaffolds in the presence of pertinent physicochemical signals, provides a promising solution to meet this demand. However, recapitulating the structural and cytoarchitectural complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
280
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(291 citation statements)
references
References 218 publications
0
280
0
1
Order By: Relevance
“…[2] In an engineered tissue construct, the cells that form the biological basis, the growth/differentiation factors that induce proper cellular functions, and the biomaterial scaffold that mimics the extracellular matrix (ECM), are the basic elements typically necessary to achieve optimal tissue biofabrication. [3, 4] In particular, the scaffold as a critical component in most scenarios, provide structural support for cell attachment, proliferation, and differentiation.…”
mentioning
confidence: 99%
“…[2] In an engineered tissue construct, the cells that form the biological basis, the growth/differentiation factors that induce proper cellular functions, and the biomaterial scaffold that mimics the extracellular matrix (ECM), are the basic elements typically necessary to achieve optimal tissue biofabrication. [3, 4] In particular, the scaffold as a critical component in most scenarios, provide structural support for cell attachment, proliferation, and differentiation.…”
mentioning
confidence: 99%
“…The results showed that these factors could effectively promote skin regeneration . The bioactive cytokines and growth factors may be a way to overcome the shortcomings of undesirable biomaterial microenvironment …”
Section: Bioactive Factorsmentioning
confidence: 99%
“…The treatments for severe skin injury that is widely used in clinics so far include autograft, allograft, and xenograft, which mean replacing the damaged skin with the patient's own skin, the donor's skin, and skin from another species, respectively. However, because of a limited number of donors, these methods can only be limited to small‐scale skin damage; therefore, alternative therapies are still needed …”
Section: Introductionmentioning
confidence: 99%
“…These nanofiber scaffolds have been combined with PSCs to engineer a variety of tissues, including neural, cardiac, and cartilage. The Willerth lab has done extensive work designing and fabricating such multifunctional scaffolds for promoting the neuronal differentiation of PSCs [47,59,69,70]. For instance, Mohtaram et al showed that encapsulation of retinoic acid inside engineered nanofibers with different topographies enhanced the neuronal differentiation of mouse iPSCs while guiding the outgrowth of neurites from these cells along the scaffold topography [55].…”
Section: Tissue Engineering Applications Of Fiber-based Scaffoldsmentioning
confidence: 99%
“…These applications include culturing fibroblasts and engineering replacements for damaged tendons. The Willerth lab in collaboration with Dr. Martin Jun's research group at Purdue University used a customized melt electrospinning setup to fabricate electrospun scaffolds with novel topographies for promoting the differentiation of PSCs into neural tissue [59,69,70,[92][93][94][95][96]. Such scaffolds can be designed and fabricated to meet needs of the consumer by altering parameters like needle size, collection distance and voltage field, which can be tuned to meet specifications provided by a customer [46].…”
Section: Tissue Engineering Applications Of Fiber-based Scaffoldsmentioning
confidence: 99%